Contribution á l’étude phytosociologique des matorrais de Méditerranée orientale - Barbero, Marcel; Quèzel, Pierre (Lazaroa, 1989)
The authors define, from 180 relevés made in the Eastern Mediterranean region, some phytosociological unities related lo the matorrals of Greece, Turkey, Cyprus, Syria and Lebanon. They especially describe the Hyperico empetrifoliae-Micromerion graecae and Helichryso sanguinei-Origanion syriaci which respectively regroup 3 sub-alliances and 5 associations and 3 sub-alliances and 12 associations. ln connection with this they discuss the phytosociological and ecological significance of the units relaled to the Cisto-Micromerietea in the Eastern Mediterranean region. (In French)